A systematic literature review of LASA error interventions. Issue 2 (15th December 2020) - Bryan, Rachel; Aronson, Jeffrey K.; Williams, Alison J.; Jordan, Sue
Abstract : Aims: The aim of this systematic review was to explore and evaluate the efficacy of interventions to reduce the prevalence of look‐alike, sound‐alike (LASA) medication name errors. Methods: We conducted a systematic review of the literature, searching PubMed, EMBASE, Scopus and Web of Science up to December 2016, and re‐ran the search in February 2020 for later results. We included studies of interventions to reduce LASA errors and included randomized controlled trials, controlled before‐and‐after studies, and interrupted time series. Details were registered in Prospero (ID: CRD42016048198). Results: We identified six studies that fulfilled our inclusion criteria. All were conducted in laboratories. Given the diversity in the included studies, we did not conduct a meta‐analysis and instead report the findings narratively. The only intervention explored in RCTs was capitalization of selected letters ("Tall Man"), for which we found limited efficacy and no consensus. Conclusions: Tall Man lettering is a marginally effective intervention to reduce LASA errors, with a number of caveats. We suggest that Tall Man gives rise to a "quasi‐placebo effect", whereby a user derives more benefit from Tall Man lettering if they are aware of its purpose. Keywords: (on scholar one).